Effect of different forms of tobacco on the oral microbiome in healthy adults: a systematic review - Senaratne, Nikitha Lalindri Mareena; Yung on, Cheng; Shetty, Naresh Yedthare; Gopinath, Divya (Frontiers in Oral Health, 2024)
Objective The study aimed to evaluate the impact of tobacco use on the composition and functions of the oral microbiome in healthy adult humans. Methods We conducted a systematic search on PubMed, Web of Science, and Cinhal databases for literature published until 15 December 2023, to identify studies that have evaluated the oral microbiome with culture-independent next-generation techniques comparing the oral microbiome of tobacco users and non-users. The search followed the PECO format. The outcomes included changes in microbial diversity and abundance of microbial taxa. The quality assessment was performed using the Newcastle–Ottawa Scale (NOS) (PROSPERO ID CRD42022340151). Results Out of 2,435 articles screened, 36 articles satisfied the eligibility criteria and were selected for full-text review. Despite differences in design, quality, and population characteristics, most studies reported an increase in bacterial diversity and richness in tobacco users. The most notable bacterial taxa enriched in users were Fusobacteria and Actinobacteria at the phylum level and Streptococcus, Prevotella, and Veillonella at the genus level. At the functional level, more similarities could be noted; amino acid metabolism and xenobiotic biodegradation pathways were increased in tobacco users compared to non-users. Most of the studies were of good quality on the NOS scale. Conclusion Tobacco smoking influences oral microbial community harmony, and it shows a definitive shift towards a proinflammatory milieu. Heterogeneities were detected due to sampling and other methodological differences, emphasizing the need for greater quality research using standardized methods and reporting. Systematic Review Registration CRD42022340151.